2022
DOI: 10.4081/jphr.2021.2169
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Traumatism and Occupational Morbidity in Mining Industry of Kazakhstan

Abstract: This article presents data in the dynamics on industrial injuries and occupational morbidity in the mining industry of the Republic of Kazakhstan. The aim of this study is to analyze occupational injuries and occupational diseases between 2008 and 2018. An analysis of the number of victims of accidents, including those who died from accidents at work during the period, shows indicators of occupational injuries in the gender aspect, the outcome of accidents by degrees of severity and the material consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thus, the analysis of literature data of both foreign and domestic authors made it possible to reveal that in order to assess the health of the working population as a whole, it is necessary to study comprehensively from the standpoint of occupational health and safety. A review of special scientific literature showed that the issues of organising the occupational health and safety service have not been studied, including the insufficiently developed monitoring system for the quality of professional activity, health and life of men employed in the main industries in the Republic of Kazakhstan (Kraus et al 2019, Matsuzaki et al 2020, Ballin et al 2020, Rohwer et al, 2022Nurbek et al, 2022;Nabirova et al, 2022;Durdyev et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the analysis of literature data of both foreign and domestic authors made it possible to reveal that in order to assess the health of the working population as a whole, it is necessary to study comprehensively from the standpoint of occupational health and safety. A review of special scientific literature showed that the issues of organising the occupational health and safety service have not been studied, including the insufficiently developed monitoring system for the quality of professional activity, health and life of men employed in the main industries in the Republic of Kazakhstan (Kraus et al 2019, Matsuzaki et al 2020, Ballin et al 2020, Rohwer et al, 2022Nurbek et al, 2022;Nabirova et al, 2022;Durdyev et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nurbek et al [ 8 ] used statistical analyses to analyze occupational injuries and diseases in the mining industry in the Republic of Kazakhstan between 2008 and 2018, noting that good working conditions, attention to employee welfare, and the improvement of monitoring indicators related to labor protection contributed to a reduction in the level of industrial injuries and occupational diseases. Erdal Özer et al [ 9 ] employed statistical analyses to assess fatal accidents at Zonguldak Coal Mine in Turkey during 2005–2008, assessing the age of the cases, the mechanisms of injury, the wound sites, the causes of death, and the legality of the mine.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the presence of any negative effect disrupts the equilibrium and results in casualties. The recurrence of mining-related injuries, however, cannot be attributed to a single factor [ 8 , 9 ]. Coupling and correlation with existing factors in a multidimensional space under suitable conditions and time, accidents and injuries will occur [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation